Do Calcium and Vitamin D Levels in Blood Predict Clinical Features and/or Response to Treatment in People with Psoriasis? - Waghid, Sihan (Department of Medicine, 2023)
Context: Psoriasis is an immune-mediated skin disease which is chronic and inflammatory, with multiple clinical types and variable severity. It is renowned for its significantly negative effect on quality of life and presents with recurrent relapses and remissions. The selection of treatment of psoriasis is dependent on the psoriasis type, impact on the individual and the severity of the disease. Variable factors that remain incompletely understood influence response to systemic treatment. It is of interest to establish whether calcium or vitamin D serum levels are linked with response to treatment in people with variable (moderate to severe) psoriasis in our population. Aims: This study aims to establish whether: 1. Clinical type or severity of psoriasis is correlated with serum calcium or vitamin D; 2. Calcium or vitamin D serum levels and response to treatment with systemic agents, including methotrexate, cyclosporine, acitretin and ultraviolet light, are associated in people with variable (moderate to severe) psoriasis; 3. Calcium and vitamin D serum levels differ in psoriatic patients compared with such levels in a control group. Materials and methods: As a case control (prospective) study, one hundred people (n = 100) were recruited, fifty having psoriasis and fifty control subjects. The psoriatic participants began a new systemic treatment and/or ultraviolet light for moderate to severe psoriasis. On the basis of a PASI score at both baseline and a three-month follow-up, response to treatment was assessed. The calcium and vitamin D serum levels were measured in psoriatic patients and controls. The collected blood samples were processed by the National Health Laboratory Services. Data collected from interviews, examination and laboratory results were recorded on a data capture sheet. The study was planned to be conducted for one year, but, due to the coronavirus pandemic, it was extended into a second year. For the psoriasis group, visits at one month and three months were recorded. Standard psoriasis treatment was provided by the dermatology health care professionals at Groote Schuur Hospital. ANOVA statistics and the Chi-squared test were applied to determine whether there is a correlation between variables. Results: No significant difference in calcium serum levels was found in psoriatic patients with different types of psoriasis (p = 0.63) or in those with varying severity of psoriasis (p = 0.48). A significant difference in the vitamin D serum levels in relation to different types of psoriasis (p = 0.62) or the severity of psoriasis (p = 0.31), was also absent. Psoriatic patients' response to treatment were less in those patients with low vitamin D serum levels. People with a higher vitamin D level had a significantly greater change in the PASI score (p = 0.01). No correlation was seen between calcium serum levels and changes in PASI score at follow-up. In other words no relationship between serum calcium level and response to treatment in psoriasis (p = 0.49) was found. This study exhibited no difference in calcium levels between the control group and psoriatic group (p = 0.79). However, there were significantly lower vitamin D levels in the psoriatic group compared to the controls (p = 0.01). The mean vitamin D level was 49,92 nmol/L in the control group (SD 20.69) and the mean vitamin D level in the psoriatic group equalled 39.82 nmol/L (SD 19.49). Conclusion: We established that psoriatic patients had lower vitamin D serum levels than controls and psoriatic patients with higher vitamin D serum levels responded better to systemic treatment. However, our findings are limited by small numbers and further studies need to be performed to corroborate this result. It is possible that treatment with Vitamin D could improve outcomes in our patients. This study demonstrated that calcium serum levels did not differ between the two groups and did not correlate with response to systemic treatment.